Optimizing Finite Element Models for Concrete Bridge Assessment With Proof Load Testing - Lantsoght, Eva O. L.; de Boer, Ane; van der Veen, Cor; Hordijk, Dick A. (Frontiers in Built Environment, 2019)
Proof load testing of existing reinforced concrete bridges is becoming increasingly important as the current bridge stock is ageing. In a proof load test, a load that corresponds to the factored live load is applied to a bridge structure, to directly demonstrate that a bridge fulfils the code requirements. To optimize the procedures used in proof load tests, it can be interesting to combine field testing and finite element modelling. Finite element models can for example be used to assess a tested structure after the test when the critical position could not be loaded. In this paper, the case of viaduct De Beek, a four-span reinforced concrete slab bridge, is studied. Upon assessment, it was found that the requirements for bending moment are not fulfilled for this structure. This viaduct was proof load tested in the end span. However, the middle spans are the critical spans of this structure. The initial assessment of this viaduct was carried out with increasingly refined linear finite element models. To further study the behavior of this bridge, a nonlinear finite element model is used. The data from the field test (measured strains on the bottom of the concrete cross-section and in the steel reinforcement, as well as measured deflection profiles) are used to update the nonlinear finite element model for the end span, and to improve the modelling and assessment of the critical mid spans of the structure. Similarly, an improved assessment based on a linear finite element model is carried out. The approaches shown for viaduct De Beek should be applied for other case studies before recommendations for practice can be formulated. Eventually, an optimized combination of field testing and finite element modeling will result in an approach that reduces the cost of field testing.